Calculation of surface leakage currents on high voltage insulators by ant colony algorithm-supported FEM - Ozturk, Dursun; Cebeci, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2015)
The weakness of the outer insulation at high voltages is the reduction of the surface resistance as a result of the environmental pollution yielding formation of flashover due to the surface leakage currents. In this study, it was shown how to calculate the surface leakage currents resulting in flashover in polluted insulators and therefore power cuts by means of the ant colony algorithm (ACA). For this purpose, first, field distribution on the sample insulator surface in question was defined by the Laplace equation ( del(2) V = 0). With the help of the finite element method (FEM), the Laplace equation was obtained as an equation with a complex coefficient as a complex dielectric coefficient was used in the problem, which was converted to a set of linear equations. The solution of this problem was performed by FEM. For this purpose, a 2D finite element mesh was constructed for the area in question and the voltages at the nodes of this mesh were calculated. The current value was then calculated by transferring these voltages to the open model (AR model) obtained from the 3D model of the insulator. The ACA was used in the current calculations. After certain values of the leakage current, dry bands formed on the surface where partial arcs occurred as a result of the increase in voltage drops. Accordingly, rapid variations occurred in the current values and the electric field strengths. These variations, appearing until the formation of an arc throughout the whole leakage current distance, were calculated gradually by the ACA. The results obtained were presented graphically.
Keywords: High voltage insulator; pollution flashover; dynamic arc model; ant colony algorithm